2019
DOI: 10.17159/sajs.2019/5534
|View full text |Cite
|
Sign up to set email alerts
|

The colourful chemistry of South African latrunculid sponges

Abstract: Marine sponges – in common with many other sessile marine invertebrates seemingly devoid of obvious physical forms of defence against predators, e.g. spines or shells – are the sources of a diverse array of organic chemical compounds known as marine natural products or secondary metabolites. Recent research has indicated that the production of natural products via cellular secondary metabolic pathways in some sponge species may not occur within the sponge cells themselves, but rather in microbial endosymbionts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…biannulata Topsent, 1892 [ 130 ] and S . insignis Topsent, 1890 [ 131 ], all from the Atlantic Ocean, specifically Floridian waters, and the Azores archipelago [ 25 , 132 ]. Sceptrella was compared to the monospecific Aleutian Islands genus, Latrunculava Kelly, Reiswig & Samaai, 2016, also with a second spicule form, the “sceptre”, in addition to the anisodiscorhabd first recorded from the Oamaru Diatomite (Eocene) of New Zealand [ 21 ].…”
Section: Chemical Investigations Of Marine Sponges From Family Latmentioning
confidence: 99%
See 1 more Smart Citation
“…biannulata Topsent, 1892 [ 130 ] and S . insignis Topsent, 1890 [ 131 ], all from the Atlantic Ocean, specifically Floridian waters, and the Azores archipelago [ 25 , 132 ]. Sceptrella was compared to the monospecific Aleutian Islands genus, Latrunculava Kelly, Reiswig & Samaai, 2016, also with a second spicule form, the “sceptre”, in addition to the anisodiscorhabd first recorded from the Oamaru Diatomite (Eocene) of New Zealand [ 21 ].…”
Section: Chemical Investigations Of Marine Sponges From Family Latmentioning
confidence: 99%
“…Sceptrella was compared to the monospecific Aleutian Islands genus, Latrunculava Kelly, Reiswig & Samaai, 2016, also with a second spicule form, the “sceptre”, in addition to the anisodiscorhabd first recorded from the Oamaru Diatomite (Eocene) of New Zealand [ 21 ]. Species of Sceptrella are morphologically similar to Latrunculia and Strongylodesma species, with a cakey, dense and compressible texture, and a hemispherical or spherical body shape [ 132 ]. Sceptrella species are deep-sea organisms, having been recorded from a depth of 2460 m in some regions (e.g., the north coast of Norway) [ 25 ].…”
Section: Chemical Investigations Of Marine Sponges From Family Latmentioning
confidence: 99%
“…In 1949 the university became the University of Natal until 2004, when a merger formed the current University of KwaZulu‐Natal. It was here where Frank Warren began his work on pyrrolizidine alkaloids, and in the following years, his contribution to alkaloid chemistry, particularly those related to livestock losses, earned him local and international recognition, including a DSc from his alma mater . When Frank Warren retired from the University of Natal in 1965 to start a post as the first permanent Dean of Science at the University of Cape Town, he had supervised 62 of the 102 MSc and PhD students who had graduated from the department since his arrival .…”
Section: Professor Frank L Warrenmentioning
confidence: 99%
“…The Frank Warren lecture is an exclusive invitation extended to an organic chemist currently practicing in South Africa, who has made an outstanding contribution to the field. The first Frank Warren lecture was given by Prof. Doug Rivett (Rhodes University), and has since become a list of the most distinguished organic chemists in the country.…”
Section: History Of the Conferencementioning
confidence: 99%
“…The first marine biodiscovery program was centred at a South African university. This program, a scuba collection of approximately a dozen marine sponges, was initiated by a Rhodes University ichthyologist team from a subtidal reef in the Tsitsikamma National Park, situated on the Southern Cape coast of South Africa during the spring of 1990 [ 6 ]. It was observed that sponge metabolites' primary biological activities were to kill or prevent the growth of microbial pathogens [ 7 ].…”
Section: Introductionmentioning
confidence: 99%